Metodologia para avaliação de incerteza na medição de propriedades termofísicas pelo método flash laser: método de monte carlo aplicado a modelos dinâmicos de saída multivariável - Pablo Andrade Grossi (2008)
The Laser Flash Method has been considered by INMETRO, NPL, NIST, PTB and other organizations as a standard method for thermal diffusivity measurements. Despite its several advantages, inherent experimental features become obstacles to a coherent expression of the measurement results. In this work, an effective methodology for uncertainty evaluation of thermophysical properties measurements based on the laser flash method is presented. Such methodology is based on Monte Carlo Method (MCM) applied to a central thermal diffusion model that consider all real initial and boundary conditions form a physical model. As results, the material thermophysical properties andassign uncertainties are evaluated by a stochastic, dynamic and multivariate output model. The developed model and methodology was validated by standard samples Method carried out in the LMPT Laboratório de Medição de Propriedades Termofísicas (thermophysical properties measurement laboratory) of the Nuclear Technology Development Center (CDTN/CNEN - Brazil). The definition of a consistent and robust methodology to evaluate statistical properties involving multivariate input and multivariate output quantities of a generic model is the main result in this work. In a generic way, this methodological structure can perform the propagations of uncertainties of a central model for any real phenomenon or process.